2016
DOI: 10.1111/apa.13425
|View full text |Cite
|
Sign up to set email alerts
|

Single‐centre study reports a 84% five‐year overall survival rate for paediatric solid tumours

Abstract: The treatment results in our study are comparable with those previously published. A comprehensive local database allows for a timely follow-up of the characteristics and quality of treatment of childhood malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The overall range of diagnoses mirrored the transitional phase for the age group, with decreasing haematopoietic malignancies and increasing solid cancers. The 5‐year OS of 84% compared well with local and international studies of children and adolescents 2,5 . Males had more unfavourable outcomes, as they accounted for 81.3% of haematopoietic malignancies.…”
Section: All Subjects (%) Solid Haematopoietic Cnsmentioning
confidence: 65%
See 1 more Smart Citation
“…The overall range of diagnoses mirrored the transitional phase for the age group, with decreasing haematopoietic malignancies and increasing solid cancers. The 5‐year OS of 84% compared well with local and international studies of children and adolescents 2,5 . Males had more unfavourable outcomes, as they accounted for 81.3% of haematopoietic malignancies.…”
Section: All Subjects (%) Solid Haematopoietic Cnsmentioning
confidence: 65%
“…The 5‐year OS of 84% compared well with local and international studies of children and adolescents. 2 , 5 Males had more unfavourable outcomes, as they accounted for 81.3% of haematopoietic malignancies.…”
mentioning
confidence: 99%
“…The population-based EUROCARE-5 project [55] running from 1999-2007 reported no significant difference in survival times among children with various solid tumors. Similarly, in a single-center study in Finland comparing the periods 1990-1999 and 2000-2015 [60], the authors reported no significant change in survival times even with the improvements in diagnosis and treatment. Contrarily, a report from the Swedish Childhood Solid Tumour Working Group [58] and the Texas Cancer Registry [61] showed significant improvements in survival times.…”
Section: Plos Onementioning
confidence: 92%
“…Contrarily, a report from the Swedish Childhood Solid Tumour Working Group [58] and the Texas Cancer Registry [61] showed significant improvements in survival times. Other factors such as cancer stage [60,61], the prognostic molecular and genetic basis of cancer [62,63], the availability of treatment modalities, and response to treatment can impact the survival outcomes of children with solid tumors. Patients with advanced-stage cancer usually have adverse outcomes.…”
Section: Plos Onementioning
confidence: 99%